Transfer zones in an oblique back‐arc basin setting: Insights from the Latium‐Campania segmented margin (Tyrrhenian Sea). Issue 1 (20th January 2017) - Conti, A.; Bigi, S.; Cuffaro, M.; Doglioni, C.; Scrocca, D.; Muccini, F.; Cocchi, L.; Ligi, M.; Bortoluzzi, G.
Abstract: New multichannel seismic reflection profiles were acquired to unravel the structure of a portion of the eastern margin of the Tyrrhenian basin. This extensional feature is part of an Oligocene to Present back‐arc basin in the hangingwall of the west directed Apennines subduction system. The basin provides excellent conditions to investigate the early stage processes leading to the development of rifted passive margins and to the emplacement of oceanic crust in an oblique setting. The interpreted post‐stack‐migrated seismic profiles highlight the geometry and kinematics of the Pontine escarpment that connects the Latium‐Campania continental margin to the Vavilov basin. The latter is the main feature of the area, related to the early Pliocene extension of the Tyrrhenian Sea. Several morphological variations are pointed out along strike, mirroring different structural settings of the margin itself: a steeper margin to the north corresponds to high‐angle possibly transtensional faults, whereas a smooth slope in the southern portion corresponds to several more distributed listric faults. This work contributes to the understanding of the interplay between extensional and transtensional tectonics along the margins of an oblique back‐arc basin. Key Points: Interpretation of new multichannel seismic profiles acquired in the eastern margin of the Tyrrhenian Sea Reconstruction of the geometric and kinematics aspects of a segmented back‐arc margin Interaction between extensional and transtensional tectonics along an oblique back‐arc basin setting